2016
DOI: 10.1002/admi.201600211
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Thermal Conductance across Hydrogen‐Bonded Graphene/Polymer Interfaces

Abstract: the exceptional thermal properties of graphene and nanotubes, thereby reducing the overall conductivities of the nanocomposites.To improve the interfacial thermal conduction, interfaces between dissimilar materials need to be engineered for reduced phonon scattering. Current approaches include, but are not limited to, controlling interfacial adhesion, [16][17][18] improving interfacial stiffness, [ 19,20 ] strengthening interfacial interactions, [ 21,22 ] and manipulating phonon modes. [23][24][25] For graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 66 publications
3
31
0
Order By: Relevance
“…It is well established that TBC depends on the bonding strength at the interface, which has been predicted by analytical models [36], molecular dynamics simulations [37][38][39][40][41] and experiments [42][43][44][45]. In this study, the observed increase in G is most likely caused by an increase in adhesion between the metal and polymer.…”
Section: Resultssupporting
confidence: 53%
“…It is well established that TBC depends on the bonding strength at the interface, which has been predicted by analytical models [36], molecular dynamics simulations [37][38][39][40][41] and experiments [42][43][44][45]. In this study, the observed increase in G is most likely caused by an increase in adhesion between the metal and polymer.…”
Section: Resultssupporting
confidence: 53%
“…G-32PVA), interfacial thermal conductance is improved to be 6.22 times that of the pristine graphene/PMMA interface (551.53 MW m -2 K -1 versus 88.66 MW m -2 K -1 ). Compared with the previously studied hydroxyl-functionalized graphene/PMMA interface which features a 2D hydrogen bond layer, 27 the present system with a 3D hierarchical hydrogen bond network improves the interfacial thermal conductance further by 1-2 times, especially when X < 16. As demonstrated in Fig.…”
Section: Validationmentioning
confidence: 66%
“…As a result, grafting PVA chains improves interfacial thermal conductance, with more heat conducted through the highly efficient PVA-PMMA channel; while at low grafting densities, most heat is conducted through the less efficient graphene-PMMA channel. A direct proof of this conclusion can be obtained by computing integrated autocorrelation of interfacial heat power 27 which is proportional to interfacial thermal conductance according to Green-Kubo fluctuation theorem. Fig.…”
Section: Mechanisms Of Thermal Enhancementmentioning
confidence: 99%
“…33,34 Besides, recent theoretical and experimental studies have proven that the interfacial interactions between PMMA and GR exhibit enhanced electrical conductivity and mechanical and thermal properties. [33][34][35] More evidences can be found in the FTIR spectra (Figure 4b), which demonstrates a broad and strong peak at ~3443 cm −1 assigned to a strong hydrogen bonding in comparison with PMMA spectrum; meanwhile, the typical absorptions in the stretching regions of PMMA at ~1731 cm −1 (C=O) and 1272~1150 cm −1 (C-O-C) 36,37 generate a red shift to ~1635 cm −1 and 1232~1120 cm −1 , respectively. Those favorable interactions between PMMA and GMH composite not only ensure that active materials could be tightly attached to current collector, but also buffer the volume expansion and internal strain of active materials, which is beneficial to maintain the structural integrity of electrode.…”
Section: Performance Of Gmh-pvdf Inmentioning
confidence: 99%